1990
DOI: 10.1093/ajcp/93.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Immunohistochemical Characteristics of Bronchial Gland Cell Type Adenocarcinoma of the Lung

Abstract: Twenty-three cases of bronchial gland cell (BGC) type lung adenocarcinoma were examined clinicopathologically and immunohistochemically. BGC type adenocarcinoma was defined as adenocarcinoma showing histologic and cytologic differentiation toward the bronchial gland. This type of adenocarcinoma occurred more frequently in younger patients (mean age, 50.5 years) than in patients with other types of adenocarcinoma (mean age, 60.1 years). It had a tendency to arise from relatively large bronchi and show endobronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…We found that 25% of acinar adenocarcinoma and 3% of solid adenocarcinoma with mucin showed intracytoplasmic SP-A staining of the tumor cells. In our study, the percentage of SP-A-positive cases of adenocarcinoma without bronchioloalveolar patterns is lower than in the reports by Ueno et al [2], by Sugiyama et al [16]and by Hirata et al [13], possibly because we excluded adenocarcinoma with mixed subtypes showing bronchioloalveolar or papillary components from this study, and because we very carefully discriminated the SP-A-positive staining of hyperplastic type II cells surrounding the tumors or entrapped in the tumor from the intracytoplasmic positive SP-A stain of tumor cells [20], which sometimes can be difficult.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…We found that 25% of acinar adenocarcinoma and 3% of solid adenocarcinoma with mucin showed intracytoplasmic SP-A staining of the tumor cells. In our study, the percentage of SP-A-positive cases of adenocarcinoma without bronchioloalveolar patterns is lower than in the reports by Ueno et al [2], by Sugiyama et al [16]and by Hirata et al [13], possibly because we excluded adenocarcinoma with mixed subtypes showing bronchioloalveolar or papillary components from this study, and because we very carefully discriminated the SP-A-positive staining of hyperplastic type II cells surrounding the tumors or entrapped in the tumor from the intracytoplasmic positive SP-A stain of tumor cells [20], which sometimes can be difficult.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast to Mizutani et al [7], who concluded that only tumors with alveolar type II and/or Clara cell type are SP-A positive, our results support the theory [13, 22]that SP-A-producing cells may generate not only bronchioloalveolar and papillary carcinoma, but also other subtypes of lung adenocarcinoma such as lung acinar adenocarcinoma and solid adenocarcinoma with mucin.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Only a few cases were described as pure SRCC. Several investigations suggest that lung SRCCs are closely related to bronchial gland cell-type adenocarcinomas rather than to the goblet-cell type in terms of histogenesis and differentiation [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of pIgR expression is a common feature of adenocarcinomas originating from mucosal tissues, including the colon (Poger et al, 1976;Rognum et al, 1980Rognum et al, , 1982Isaacson, 1982b;Arends et al, 1984;Wiggers et al, 1988;Koretz et al, 1994;Krajci et al, 1996;Traicoff et al, 2003), esophagus (Gologan et al, 2008), and lung (Harris and South, 1981;Brooks and Ernst, 1984;Espinoza et al, 1984;Loosli and Hurlimann, 1984;Kodama et al, 1985;Kondi-Paphitis and Addis, 1986;Popper et al, 1987;Kawai et al, 1988;Ordonez, 1989;Hirata et al, 1990;Ishida et al, 1990a,b;Brown et al, 1993;Khattar et al, 2005;Ocak et al, 2012). Two studies using microarray analysis to identify gene expression biomarkers for colorectal cancer reported that decreased pIgR mRNA levels in metastatic tumors (Jorissen et al, 2009) and colonic biopsies (Agesen et al, 2012) were associated with poor prognosis.…”
Section: Dysregulation Of Pigr Expression In Disease Statesmentioning
confidence: 99%